Relativas livres transparentes em Português: algumas reflexões sintáticas - Brito, Ana (Revista da Associação Portuguesa de Linguística, 2022)
The goal of this paper is to analyse the syntax of a group of free relatives called “transparent free relatives” (TFR) in European Portuguese. Starting from several properties, we will argue in favour of the hypothesis that the “pivot” of TFR is the wh word and not the predicate of the free relative (FR). Such morpheme is the invariable constituent o que, the most unspecified of wh morphemes in Portuguese. As in all FR, there is a null D (or a D occupied by a determiner) that selects a CP complement, which makes it unnecessary to propose a null antecedent pro. In order to explain the invariable and inseparable o que, we follow Medeiros Júnior (2016), for whom this morpheme is the result of reanalysis in Contemporary European Portuguese. We also develop the idea that they always involve a small clause expressed by a copulative verb, mainly ser ‘to be’, they are therefore predicative and they are, most of the times, indefinite, but they also may contain a definite expression, as already argued for Portuguese by Ferreira (2007).